Implementasi Project Based Learning Berbasis Lingkungan Pada Materi Keanekaragaman Hayati - Anisia Sirken (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the effect of implementing Environment-Based Project Based Learning (PjBL) on students’ learning outcomes and learning activities in biodiversity topics. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects consisted of two classes: an experimental class that applied Environment-Based Project Based Learning and a control class that used conventional learning methods. Research instruments included learning achievement tests, student activity observation sheets, and project assessment rubrics. Data were analyzed using descriptive and inferential statistics, including a t-test at a significance level of 0.05. The results indicated a significant difference in learning outcomes between the experimental and control groups, with the experimental group showing higher improvement in learning achievement. In addition, students’ learning activities in the experimental class were categorized as good to very good. The implementation of Environment-Based Project Based Learning also enhanced students’ environmental awareness and active involvement in the learning process. Therefore, Environment-Based Project Based Learning is effective for biology learning, particularly in biodiversity material.